A arqueologia das ciências naturais nos anos iniciais do ensino fundamental a partir das propostas pedagógicas da SEMED - Silva, Shirley Vitor da (2022)
The research has as object the study of Natural Sciences in the first years of Elementary School, with the objective of problematizing the historical and regulatory trajectories of the Natural Sciences in the pedagogical proposals of the first years of the Elementary School in SEMED Manaus, highlighting the conceptions of Science present in this curricular component. The study is based on post-critical theory, with which we invent a new way of doing and saying our research. We approach the studies of the Philosophy of Difference, especially in Foucault's tools as a theoretical-methodological foundation for thinking about science teaching. We created an archeology of research that allowed us to dig into the documents analyzing the discourses as monuments built there. We developed a conceptual approach to the curriculum in the post-critical perspective, and more specifically to the science curriculum in the early years. We intertwined understandings about a curriculum that is a field of disputes, in which knowledge-power relations are established. We observed that science teaching is built from continuities and ruptures; that in the educational space, teaching is regulated so that truths can be established. When approaching such fossils that are said to be under a critical, socio interactionist, constructive view, we point out that they use technicist strategies, emphasize the development of certain intellectual acquisitions and evaluate skills and abilities in a traditionalist way. This allows us to affirm that Science Teaching in SEMED Manaus' proposals seem to become increasingly captive of episodic and successive demands and, not infrequently, present their objectives designed to meet random fads. All this in the quest to meet the formative requirements of economic, political and social discourses that preach updating, self responsibility and adaptation. Excavating in SEMED's Pedagogical Proposals and analyzing the trajectory of the Science component has brought us other possibilities to problematize the conditions of existence of other fossils in this field and the subject that is produced in it and/or from it in different constructions to look with suspicion at the monuments that are built in the so-called normative documents, to deconstruct the truths that are regulated in them. These are some layers that may be excavated in new expeditions. Keywords: curriculum; natural Sciences; early years; speech; Michel Foucault.